Study of Serum Uric Acid Levels in Thyroid Dysfunctions - Bhattarai, Anshu; Kathayat, Goma; Karmacharya, Poonam; Tiwari, Indu; Singh, Surjit (Medical Journal of Eastern Nepal, 2023)
Background: Hyperuricemia in thyroid dysfunctions has been linked to either impaired renal handling of uric acid or overproduction of uric acid. This study aimed to determine the serum uric acid levels in patients with thyroid dysfunction and to determine the link between thyroid dysfunction and hyperuricemia. Methods: This prospective and quantitative study which was conducted at Department of Biochemistry, Manipal Teaching Hospital determined the serum uric acid concentrations of 30 years or older; male or female participants diagnosed with either hypothyroidism or hyperthyroidism. T3 and T4 was determined by chemiluminiscence immunoassay (CLIA) and OCD VITROS dry chemistry analyzer was used to determine serum uric acid level. Data entry and analysis was done using SPSS version 23. Descriptive statistics using frequency with percentage and inferential statistics using non-parametric tests were used. Results: In a total of 100 participants, prevalence of hyperuricemia was 42% (31% in hypothyroidism and 11% in hyperthyroidism). The mean serum uric acid in overall participants was 6.25 ± 2.04 (6.55 ± 1.84 in hypothyroidism and 6.05 ± 1.71 in hyperthyroidism).Significant association was seen between thyroid status and hyperuricemia (p = 0.001).Also, significant difference (p = 0.02) was seen in serum uric acid between hyperthyroid and hypothyroid patients. Conclusion: Higher prevalence rate of hyperuricemia was found among hypothyroid patients than in hyperthyroid subjects, and a significant association was found between thyroid dysfunction and hyperuricemia. This indicates need for more research to further uncover the mechanisms underlying it.